LAGU âKALI KEMIRIâ DAN âPANTAI PASIR DUAâ DALAM ALBUM BLACK BROTHERS PAPUA SEBAGAI MEDIA PEMBELAJARAN KONTEKSTUAL - Warami, Nomensen (JURNAL TRITON PENDIDIKAN, 2016)
The paper aims at revealing contextual learning obtained from songs. âKali Kemiriâ and âPasir Duaâ song in Papuan Black Brothersâ album is one source of learning media. Contextual learning helps the teacher to ties lesson materials with their application in life as family and society members.The current facts show that students only memorize the concepts and are less able to use the concepts if they find problems in real life that has relation with the concepts they have. Beside that, students are also less able to detemine and formulate problems. Many critics were sent to teachers who taught by only focussing on Â mastery of information and bare concepts. Therefore, it is hoped that contextual learning model will pay more attention in serving meaningful subjects in natural forms which can be experienced not knowledge-transferred from teachers to students.The paper focuses on revealing efforts of âKali Kemiriâ and âPantai Pasir Duaâ song in Papuan Black Brothersâ Album by projecting problems including: (i) Interest and ability of preliminary writing, (ii) theapplication of contextual learning model, and (iii) ability and completeness of writing narrative paragraph.Â